(3cJGH GdSehes - (3RfWGM GdMcjes
(3ChdgG (B:s
(3GdMeO ddg GdYdje GdMdje GdPi Od Ndbg Ydi Yde eG jMJhLhf Edjg ef eVGQge bGd RfWGM GdMcje hGVY gPG GdcJGH Efi CJjJ Ydi TLQI GdUfOd ahLOJ QjMkG WjHkG s
(3BNQgG (B:s
(3jOb hjfNd Ke jSbi ef eGA GdcfOS GdeWHhN HdHf GdYTQ SHYI CjGe MJi JMJGL Edjg Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs